Maternal and child factors of stunted children: a case control study - Hastuti, Apriyani Puji; Sukartini, Tintin; Arief, Yuni Sufyanti; Nursalam, Nursalam; Roesardhyati, Ratna; Mumpuningtias, Elyk Dwi; Hidayat, Syaifurrahman; Kurniawan, Ardhiles Wahyu (Intelektual Pustaka Media Utama, 2025)
Due to the transition or weaning process and infant feeding patterns, infants under the age of five (IYCF) are susceptible to nutritional problems, especially with regard to food diversity, diet quality, availability, and accessibility. According to fundamental health research, the mother’s capacity to supply nourishment (sources from animal and vegetable protein) and the main meal as an energy source during the first two years of life is associated. Community based case-control study was conducted among children 6-24 month. The study participant used multistage random sampling procedure, with a sample size of 180 mothers who have stunted children. This study used a questionnaire as its data research instrument, which was examined for validity and reliability utilizing data analysis methods like linear regression and SPSS 16.0 statistical software. Factor associated the role of mothers in the feeding of stunted children to nutritional status are age, educational level, occupation, motivation, mobility, decision making, knowledge, self-esteem, self-efficacy, family type, family role, stress of family, coping of family, family social support, weight of birth, responsive feeding. The all of factors can affected roles of mothers in the feeding of stunted children to nutritional status with p-value <0.005. While the child’s age, birth length, breastfeeding, feeding children are not factors associated with the role of mothers in the feeding of stunted children to nutritional status.